Studi Literatur : Pembinaan Dan Pengawasan Pemerintahan Di Daerah Kabupaten Bandung - Fajri Fhatariki Ghifari; Irvio Gafrilla Marhenza; Gandina Suciyani F. H.; Faya Zahira; Ivan Darmawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Development and supervision of regional government is an important aspect in realizing good and accountable governance. In Bandung Regency, guidance and supervision is carried out by various parties, including the central government, regional government and the community. This research aims to analyze the effectiveness of government guidance and supervision in the Bandung Regency area. The research method used is a literature study by examining various data sources, such as statutory regulations, reports on the results of coaching and supervision, and related research journals. The research results show that government development and supervision in the Bandung Regency area still has several weaknesses, such as lack of coordination between stakeholders, limited human resources, and not yet optimal use of information technology.Based on the research results, several steps are recommended to increase the effectiveness of government guidance and supervision in the Bandung Regency area, such as: Strengthen coordination between stakeholder, Improve the quality of human resources, Optimizing the use of information technology, Increase community participation in government development and supervision